The Evolution and Development process of the choir team /group/ of Inner Mongolian - Medee, Mandlaa; Danzan, Enkhtsetseg (Mongolian Journal of Arts and Culture, 2024)
This article examines the development of the Inner Mongolian choral art in China in relation to the creative activities of the “Mongolian National Youth Choir” established in 1987. Because the development of choral art in Inner Mongolia was carried out in accordance with the time, society, culture, and government policies of that time. For example, in 1945, the “Literature and Art Group” was established in China on April 1, 1946, with the aim of launching a movement to liberate Inner Mongolia. In this way, the source of choral art was laid in the field of propaganda with the aim of conveying the party’s policies to the people. As a result of this process, dozens of choral groups have been operating in Inner Mongolia. However, the “Mongolian National Youth Choir” established in 1987 is considered to have entered a new stage of development. Өвөр монголын найрал дууны бүлгэмийн хувьсал, хөгжлийн үйл явц Хураангуй: Энэхүү өгүүлэлдээ БНХАУ-ын Өвөр монголын найрал дууны бүлгэмийн үүсэл хөгжлийг 1987 онд байгуулагдсан “Монгол үндэстний залуучуудын найрал дууны бүлгэм”-ийн уран бүтээлийн үйл ажиллагаатай холбон авч үзсэн болно. Учир нь найрал дууны урлаг Өвөр монгол оронд үүсэж хөгжихдөө чухамхүү тухайн цаг үе, нийгэм соёл, төр засгийн бодлогын дагуу явагдаж, тухайлбал, 1945 онд БНХАУ-д Өвөр монголыг чөлөөлөх хөдөлгөөн өрнүүлэхээр төлөвлөн, 1946 оны 04-р сарын 01-ний өдөр “Утга урлагийн бүлгэм” байгуулан, намын бодлогыг ард түмэнд хүргэх зорилго бүхий суртал ухуулгын чиглэлээр найрал дууны урлагийн эх үүсвэр тавигдсан байдаг. Энэ үйл явцын үр дүнд Өвөр монголд найрал дууны олон арван бүлгэм ажиллаж иржээ. Харин 1987 онд байгуулагдсан “Монгол үндэстний залуучуудын найрал дууны бүлгэм”-ийн хувьд хөгжлийн шинэ шатанд гарсан хэмээн үзэж байгаа болно. Түлхүүр үгс: найрал дууны бүлгэм, уламжлал, шинэчлэл, найрал дууны урлаг